Development and assessment of pantoprazole sodium fast-dissolving tablets: A promising tablet dosage form: Research Article (Journal of Pharma Insights and Research, 2023)
Pantoprazole is a proton pump inhibitor belongs to group of benzimidazole which has been widely used in the treatment of gastric, duodenal ulcer and also in gastro-esophageal reflux disease (GERD), Zollinger Ellison syndrome. It suppresses the acid production by inhibiting the H+ K+ ATPase. In this present study, an effort has been made to formulate and evaluate of fast dissolving or rapid release tablets, of Pantoprazole Sodium using three different Superdisintegrants like Sodium starch glycolate (SSG), Croscarmellose Sodium (CCS) and Crospovidone (CP) by direct compression method using different concentration (5%, 7.5%, & 10%). The prepared tablets were evaluated pre and post compression parameter. The pre-compression parameter like Angle of repose, bulk density, tapped density, compressibility index, Hausners ratio, solubility, and melting point. The post-compression parameter like thickness, hardness, friability, weight variation, wetting time, weight volume, drug content uniformity, water absortion ratio, in-vitro disintegration time, in-vitro dispersion time, in vitro dissolution study and stability study.  The formulated tablets were evaluated for various parameter mention in above and compiled with the limits. Among all the formulations F9 containing Crospovidone with a concentration of 10% produce the least disintegrating time 24.53 sec. and dispersion time 31.71 sec. resulting in higher drug release rate 96.42% in 10 minutes. Hence it is considered an optimized formulation. The present study revealed that the Crospovidone showed better disintegrating properties then the most widely used superdisintegrants like sodium starch glycolate and croscarmellose sodium in the formulation of fast dissolving tablets